Study of Factors Influencing Consumers to adopt EVs (Electric Vehicles) - Wongsunopparat, Sumas; Cherian, Peter (Business and Economic Research, 2023)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Statista market forecast has shown that revenue in the Electric Vehicles market is projected to reach US$457.60bn in 2023. Revenue is expected to show an annual growth rate (CAGR 2023-2027) of 17.02%, resulting in a projected market volume of US$858.00bn by 2027. Electric vehicles are gaining popularity and market share. In Q2 2022, EV sales accounted for 5.6% of the total auto market (up from 2.7% in Q2 of 2021). Clean energy and improved performance are driving people to make the switch to electric. Government incentives continue to buttress the future of all things electric. Between today and 2050, the electric vehicle market opportunity is slated to rise to $53 trillion. Additionally, global electricity demand in that same year is projected to increase by 27% even though KPMG reports in December 2022 that automotive executives are less bullish than they were last year about the adoption of electric vehicles. The survey found 76% are concerned that inflation and high interest rates will adversely affect their business in 2023. For the U.S., the median expectation for EV sales was 35% of the new vehicle market by 2030 — down from 65% a year earlier. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The purpose of this research is to study factors influencing consumer to adopt Electric Vehicles. These factors include seven independent variables: Mileage (ML), Battery (BA), Charge station (CS), Price (PR), Maintenance (MT), At-home charger (HC), Government policy (GP), Promotion (PM), Brand (BR) and one dependent variable: Consumer Factor (CF). 387 sample were collected using electronic questionnaire through social media. We used Structural Equation Models (SEM) for data analysis. The result shows that since the RMSEA, which is an absolute fit index that assesses how far our hypothesized model is from a perfect model, for this model is .04 (<.05) which strongly indicates a “close fit” and the Goodness of Fit Index (GFI) value is .913 (>.90), the model seems to fit well according to the descriptive measures of fit. More importantly, Battery (BA), Charge station (CS), Price (PR), At-home charger (HC), Government policy (GP), and Brand (BR) are significantly defined as key success factors of electric vehicles (EV) from the consumer’s perspective due to their p-values are all less than .05. That means if these significant factors are taken good care of from having branded EV with quality battery at a competitive price offering with more charge stations available both in public and at home, all of which are deeply supported by government policy to encourage people to switch over to EV ASAP, EV will become much more successful and widely adopted from consumer standpoint much faster than what has been happening so far.